Recent progress on the microbial mitigation of heavy metal stress in soybean: overview and implications - Shaffique, Shifa; Hussain, Saddam; Kang, Sang-Mo; Imran, Muhammad; Kwon, Eun-Hae; Khan, Muhammad Aaqil; Lee, In-Jung (Frontiers in Plant Science, 2023)
Plants are adapted to defend themselves through programming, reprogramming, and stress tolerance against numerous environmental stresses, including heavy metal toxicity. Heavy metal stress is a kind of abiotic stress that continuously reduces various crops’ productivity, including soybeans. Beneficial microbes play an essential role in improving plant productivity as well as mitigating abiotic stress. The simultaneous effect of abiotic stress from heavy metals on soybeans is rarely explored. Moreover, reducing metal contamination in soybean seeds through a sustainable approach is extremely needed. The present article describes the initiation of heavy metal tolerance mediated by plant inoculation with endophytes and plant growth-promoting rhizobacteria, the identification of plant transduction pathways via sensing annotation, and contemporary changes from molecular to genomics. The results suggest that the inoculation of beneficial microbes plays a significant role in rescuing soybeans under heavy metal stress. They create a dynamic, complex interaction with plants via a cascade called plant–microbial interaction. It enhances stress metal tolerance via the production of phytohormones, gene expression, and secondary metabolites. Overall, microbial inoculation is essential in mediating plant protection responses to heavy metal stress produced by a fluctuating climate.